Principles of management in the case of dysphagia in the course of amyotrophic lateral sclerosis - Ożóg, Piotr; Natański, Dawid; Zukow, Walery (Journal of Education, Health and Sport, 2019)
Amyotrophic Lateral Sclerosis (ALS) is a progressive neurodegenerative disease which causes damage to the peripheral or central motor. The disease mainly includes middle-aged persons in the sixth and seventh decades of life. It is more frequent in males and takes an average of 2-3 years (causing death). ALS has an individual growing course and is difficult to diagnose. A frequent complication among patients is dysphagia (swallowing disorders). The issue may be related to the process of fasting as well as its move to the stomach. Palliative care and linked with her physiotherapy deals with symptom relief. Individual treatment aims to prevent patient malnutrition and aspiration of food into the respiratory system, which can lead to pneumonia and other complications. The process of improvement consists in striving for the longest possible physiological swallowing and later for functional swallowing. The main goal of rehabilitation for patients with dysphagia is to restore the nutrition orally effective while maintaining or compensation defensive reflexes enable respiratory protection. There are three types of therapies functional: restorative, compensatory and adaptive. When the physiotherapist's support will not be able to provide the swallowing function, it is advisable to use other supportive methods, such as gastrostomy.